Oocyte Competence of Prepubertal Sheep and Goat Oocytes: An Assessment of Large-Scale Chromatin Configuration and Epidermal Growth Factor Receptor Expression in Oocytes and Cumulus Cells - Ferrer-Roda, Mònica; Izquierdo, Dolors; Gil, Ana; Oliveira, Maria Emilia Franco [UNESP]; Paramio, Maria-Teresa (MDPI, 2024)
The oocyte competence of prepubertal females is lower compared to that of adults, mainly because they originate from small follicles. In adult females, the germinal vesicle (GV) and epidermal growth factor receptor (EGFR) have been associated with oocyte competence. This study aimed to analyze GV chromatin configuration and EGFR expression in prepubertal goat and sheep oocytes obtained from small (<3 mm) and large (≥3 mm) follicles and compare them with those from adults. GV chromatin was classified from diffuse to condensed as GV1, GVn, and GVc for goats and NSN, SN, and SNE for sheep. EGFR was quantified in cumulus cells (CCs) by Western blotting and in oocytes by immunofluorescence. Oocytes from prepubertal large follicles and adults exhibited highly condensed chromatin in goats (71% and 69% in GVc, respectively) and sheep (59% and 75% in SNE, respectively). In both species, EGFR expression in CCs and oocytes was higher in prepubertal large follicles than in small ones. In adult females, EGFR expression in oocytes was higher than in prepubertal large follicles. In conclusion, GV configuration and EGFR expression in CCs and oocytes were higher in the large than small follicles of prepubertal females.
Keywords: EGF receptor; germinal vesicle; goat; oocyte; sheep